2021
DOI: 10.3390/antibiotics10030287
|View full text |Cite
|
Sign up to set email alerts
|

Nanomotion Detection-Based Rapid Antibiotic Susceptibility Testing

Abstract: Rapid antibiotic susceptibility testing (AST) could play a major role in fighting multidrug-resistant bacteria. Recently, it was discovered that all living organisms oscillate in the range of nanometers and that these oscillations, referred to as nanomotion, stop as soon the organism dies. This finding led to the development of rapid AST techniques based on the monitoring of these oscillations upon exposure to antibiotics. In this review, we explain the working principle of this novel technique, compare the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 151 publications
(215 reference statements)
0
18
0
1
Order By: Relevance
“…Numerous studies demonstrated that living organisms attached to AFM cantilevers induce oscillations of the lever that immediately stop when the organism dies [23,24]. Hence, this newly developed technology, called cellular nanomotion detection (NMD), detects living organisms in a chemistry-independent manner and offers a clear advantage in terms of test velocity [25,26], but possesses several drawbacks too. AFMs, unfortunately, are expensive and relatively complex devices that require some expertise to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrated that living organisms attached to AFM cantilevers induce oscillations of the lever that immediately stop when the organism dies [23,24]. Hence, this newly developed technology, called cellular nanomotion detection (NMD), detects living organisms in a chemistry-independent manner and offers a clear advantage in terms of test velocity [25,26], but possesses several drawbacks too. AFMs, unfortunately, are expensive and relatively complex devices that require some expertise to operate.…”
Section: Introductionmentioning
confidence: 99%
“…Like direct AST, the AtbFinder system enables direct sampling of biological specimens without the need for culturing or time-consuming sample processing. Furthermore, the AtbFinder method can indicate suitable antibiotics in only 4 h, whereas direct AST requires 18–36 h (and that is why direct AST is not applicable for tailoring empirical antibiotic therapy) [ 86 , 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical sensors have been proposed for AST [76,98]. The forces produced by the interaction of the target species with the receptors immobilized on the cantilever determine a change in the cantilever resonance frequency that behaves as a harmonic oscillator.…”
Section: Ast Magnetic Mass and Mechanical (Bio)sensorsmentioning
confidence: 99%
“…For the determination of bacteria and their susceptibility or resistance, the cells adhere to the cantilever, and according to the added mass and position, the change in resonance frequency is monitored [74,99,100]. Currently, the atomic force microscope (AFM) is one of the main nanomechanical techniques used in AST due to its ability to detect displacements in the range of 0.1 Å and a resolution of microseconds [98,101]. Using an AFM system, Stupar et al developed a methodology capable of detecting nanomotion of E. coli bacteria and observing their behavior when exposed to ciprofloxacin, ampicillin, and ceftriaxone [102].…”
Section: Ast Magnetic Mass and Mechanical (Bio)sensorsmentioning
confidence: 99%